Blastocyst complementation using Prdm14-deficient rats enables efficient germline transmission and generation of functional mouse spermatids in rats - Toshihiro Kobayashi (Nature Portfolio, 2021)
The uptake of donor pluripotent stem cells (PSCs) in hosts of different species and subsequent germline transmission is very inefficient. Here, the authors show, using Prdm14 gene depleted rat host blastocysts to remove functional sperm, that germline transmission from donor rat or mouse PSCs is possible.